DEVELOPMENT OF THE MACHINE AND APPARATUS SCHEME FOR THE PRODUCTION OF HEALTHY, CRISPY AND SUGAR FREE FLAKES FOR THE CONFECTIONERY INDUSTRY - Коваленко, Ігор (SWorldJournal, 2024)
This article presents the development of a machinery and equipment scheme for producing nutritious, crispy flakes without the addition of sugar, suitable for use in the confectionery industry. It describes current trends in the demand for healthy food pr